Upaya Peningkatan Kompetensi Guru Dalam Pembentukan Model Matematika Di MGMP Matematika SMA Kota Bukitinggi - Media Rosha (Universitas Sarjanawiyata Tamansiswa, 2018)
Educational city Bukittinggi has some Senior High School (SMA) and they are potential.Â Learning process is doing well but not optimal yet. Mathematics teacher find the difficulties in build, solve and interprete mathematical models based and real world problem. In other case, it is one of the mathematics learning objectives for SMA. This case gives the negative impact. If teacher knows the models of a problem, she/he will use in explaining the lessson, so that the students find the benefitÂ of that mathematical concept. One way to solve this problem is give a workshop to teacher to construct mathematical model based on the real world context. In workshop teacher are teached how to model it, oriented to mathematical modelling. The objective of this workshop to help SMA mathematical teacher to model the real world problem, so that the problem solved. Workshop do with several analysis, they are analysis of need, orientation and discussion. Result that teacher reach are they are motivated to study how to model mathematical problem and they understand how to model it.